TIGA RELIEF KHARMAWIBANGGA CANDI BOROBUDUR - Hari Lelono (BRIN, 1995)
The subject is not a general discussion, but a special discussion includes case studies to reveal the phenomena carved at the foot of the Borobudur temple, or better known as Kharmawibangga. This part of the foot of the candi does not appear as a whole, because of the safety and sustainability of the temple itself, as a reinforcing material. Therefore, not everyone can see these reliefs, but from libraries by archaeologists such as Van Erp, Soekmono, and Casparis, photographic recordings can help in this study.